EFFICIENCY INVESTIGATION OF THE USE OF PYROPHYLLITE IN ENSILING MAIZE PLANT - Bočarov-Stančić, Aleksandra (Food and Feed Research, 2020)
The paper presents the results of testing the effect of pyrophyllite shale (pyrophyllite) on the quality of maize plant silage, primarily on the production of organic acids, pH value, quality assessment and microbiological safety. The ensiling was done in plastic containers which allowed the storage of 10 kg of chopped green mass. Tested pyrophyllite doses were: 0% in the control treatment (I), 0.5 and 1.0% in experimental treatments (II and III, respectively). Granulated pyrophyllite (100 µm), originating from Parsovići, Konjic site, AD Harbi Ltd., Sarajevo, Bosnia and Herzegovina, was manually incorporated. The chopped green mass of the maize plant came from FAO 600 hybrids. The green mass containing 37.17% of dry matter (final waxy ripening phase) was compressed in the same manner in all three treatments during the filling of the vessels. The containers were then covered with nylon foil (0.2 mm) above which a layer of fine sand (approx. 5 cm) was placed in toward the silage protection from air passage. The silages were opened after 7 weeks and organoleptic, chemical and microbiological analyses were performed. The organoleptic properties of silages (colour and odour) were better in silages containing 0.5 and 1.0% pyrophyllite. The silage temperature at the moment of opening of the containers was lower in the treatments with 0.5 and 1.0% added pyrophyllite (13.7 and 13.2 °C, respectively) while in the control treatment it was 14.6 °C. The addition of pyrophyllite to silage affected the production of volatile fatty acids (p ≤ 0.05). The highest amount of lactic acid was found in the silage sample without the addition of pyrophyllite, and acetic acid in the silage treated with 0.5 and 1.0% of pyrophyllite. The lowest amount of butyric acid was determined in the silage with the addition of 1% pyrophyllite. Based on the content and interrelationship of lactic, acetic and butyric acid, as well as the pH values, all three silages were rated as the highest (I) class. The number of aerobic mesophilic bacteria, as well as the number of yeasts, was lower in the silages with the addition of 0.5 and 1.0% pyrophyllite. In future, particular attention should be paid on the possibility of pyrophyllite enrichment (e.g. with nitrogen) and more appropriate physical formulation (e.g. granules) that would allow more efficient practical application.
Keywords: ensiling; maize plant; pyrophyllite